Composite, method for producing same, and filling composition for shaping using same

By using the composite prepared by biodegradable particles and water-soluble polymers whose particle size distribution is controlled, the problems of short shelf life and inconvenient operation of the filling composition for plastic surgery are solved, and long-term storage and efficient operation of the material are achieved.

CN119403581APending Publication Date: 2025-02-07KOREA FINI CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380047158.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-14
Filing Date
2023-06-14
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing filling composition for plastic surgery has a limited shelf life after use for a period of time, and its viscosity is too high or its dispersion is poor, resulting in difficulty in injection and inconvenient operation.

Method used

Complexes with good dispersion and long-term storage are prepared by controlling the particle size distribution and weight average molecular weight of the polymer using a composite including biodegradable particles and a water-soluble polymer.

Benefits of technology

The shelf life of the material is extended, the convenience of storage and processing is improved, the operator's discomfort and fatigue are reduced, and the operating environment of the filling composition for plastic surgery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119403581A_ABST
    Figure CN119403581A_ABST
Patent Text Reader

Abstract

The present invention relates to: a composite comprising biodegradable particles of which the particle size distribution (PSD) can be controlled; a method for manufacturing the composite; and a filling composition for shaping using the composite; and a water-soluble polymer. The compound of the present invention has good long-term storage and dispersibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composite composed of two or more components, a method for producing the composite, and a plastic surgery filling composition (for example, a skin plastic surgery filling composition) using the composite. Background Art

[0002] Plastic surgery is to inject a filler composition into the subcutaneous tissue or tissue to achieve the purpose of correcting human body function or shaping the body. The filler composition is preferably safe for the human body and has cell compatibility (biocompatible) and biodegradability (biodegradable).

[0003] The filler composition contains natural polymers such as collagen, gelatin, hyaluronic acid and dextran, or synthetic polymers such as polylactic acid, polyglutamic acid, polycaprolactone and polyacrylamide.

[0004] However, since the natural polymer or the synthetic polymer begins to decompose after a period of use, the filling composition containing these polymers has a limited shelf life. In addition, most filling compositions are injected with a syringe. In this case, if the viscosity of the filling composition is too high or the dispersibility is poor, it is difficult to inject the filling composition with a fine needle, and the force of the syringe (injection force) must be increased, which causes discomfort and fatigue to the operator.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Korean Patent Publication No. 2017-0123099 (November 7, 2017) Summary of the invention

[0008] Technical issues

[0009] The present invention aims to provide a composite and a method for producing the same. The composite has good long-term storage and dispersibility and can improve the operating environment of the plastic surgery filling composition.

[0010] Furthermore, the present invention is also intended to provide a plastic surgery filling composition that can be handled relatively easily.

[0011] Means of solving the problem

[0012] To solve the above problem, according to one embodiment of the present invention, a composite is provided, the composite comprising biodegradable particles; and a water-soluble polymer, wherein the particle size distribution of the biodegradable particles according to the following formula 1 is 1.0 to 2.5,

[0013] <Formula 1>

[0014] PSD = (Dv(90) - Dv(10)) / Dv(50)

[0015] In the formula 1,

[0016] Dv(10) is the size of the biodegradable particles within 10% of the distribution.

[0017] Dv(50) is the size within which 50% of the biodegradable particles are distributed.

[0018] Dv(90) is the size within which 90% of the biodegradable particles are distributed.

[0019] According to another embodiment of the present invention, a method for manufacturing a composite is provided, comprising the following steps:

[0020] (1) dissolving a biodegradable raw material in a first solvent to prepare a biodegradable solution; (2) spraying the biodegradable solution into a second solvent having a freezing point lower than that of the first solvent to form biodegradable particles; (3) screening the biodegradable particles by size; (4) adding the biodegradable particles screened by size to a water-soluble polymer solution to prepare a mixed solution; (5) filling the mixed solution into a container; and (6) freeze-drying the mixed solution filled into the container to form a composite, wherein the particle size distribution (PSD) of the biodegradable particles contained in the composite according to Formula 1 is 1.0 to 2.5.

[0021] According to another embodiment of the present invention, a plastic surgery filling composition containing the composite is provided.

[0022] Effects of the Invention

[0023] The composite according to the present invention includes biodegradable particles whose particle size distribution is controlled within a specific range, so that when dispersed in a solvent, it can be dispersed quickly and uniformly, and even during long-term storage, the degradation of the biodegradable particles and / or water-soluble polymer contained in the composite can be minimized. Therefore, when the composite according to the present invention is used as a material in a plastic surgery filling composition, the shelf life of the material can be extended and the convenience of storage and handling can be improved.

[0024] Furthermore, since the well-dispersible complex is dispersed in the plastic surgery filling composition according to the present invention, the operation process can be easily completed even if the operator (operator) applies relatively small force to the syringe.

[0025] Simple diagram description

[0026] Figure 1 is a schematic diagram of a manufacturing process of a composite according to an embodiment of the present invention.

[0027] Figure 2 These are photographs of the composite dosage forms according to Example 1, Example 5 and Comparative Example 1 in Confirmation Experimental Example 1.

[0028] Figure 3 This is a photograph of a cross section of the composite according to Example 1 confirmed by scanning electron microscopy in Experimental Example 6.

[0029] Figure 4 This is a photograph of a cross section of the composite according to Example 5 confirmed by scanning electron microscopy in Experimental Example 6.

[0030] Best Mode for Carrying Out the Invention

[0031] The present invention will be described in detail below, wherein the present invention is not limited to the contents disclosed below but can be modified in various forms without changing the essence of the present invention.

[0032] The word "comprising" in this specification is intended to specify certain features, regions, steps, processes, elements and / or components, and does not exclude the existence or addition of other features, regions, steps, processes, elements and / or components unless specifically stated to the contrary.

[0033] In the present specification, a description that one component is connected or coupled to another component includes both direct connection or coupling between these components and indirect connection or coupling with other components.

[0034] Unless the context indicates otherwise, a singular expression in the present specification should be construed as including the singular or the plural.

[0035] Unless otherwise indicated, all numbers and expressions indicating amounts of ingredients, reaction conditions, etc. in this specification may be expressed as "about".

[0036] The terms "first", "second" and the like in the present specification are used to describe various components, and each component is not limited by these terms, and these terms are only used to distinguish one component from another.

[0037] Compound

[0038] The composite of the present invention may be a combination of materials having cell compatibility and / or biodegradability, etc. Specifically, the composite of the present invention comprises biodegradable particles whose particle size distribution (PSD) is controlled within a specific range and a water-soluble polymer, as described below.

[0039] Biodegradable particles

[0040] According to the present invention, the biodegradable particles contained in the composite have the function of restoring or replacing damaged or aged human tissues (such as skin tissues).

[0041] According to the following formula 1, the particle size distribution (PSD) of the biodegradable particles is 1.0 to 2.5. Specifically, according to the following formula 1, the particle size distribution of the biodegradable particles can be 1.0 to 2.3, 1.01 to 2.0, 1.02 to 1.9, 1.03 to 1.95, 1.04 to 1.9, 1.05 to 1.8, 1.05 to 1.6, 1.05 to 1.5, 1.08 to 1.4, 1.09 to 1.3 or 1.1 to 1.3, but not limited thereto. Since the particle size distribution of the biodegradable particles is within the above range, the composite containing the biodegradable particles can have good dispersibility in a solvent. In particular, when the composite involved in the present invention is used as a material for a plastic filling composition, due to the good dispersibility of the composite, the plastic filling composition can be prepared in a short time. In addition, since the biodegradable particles are uniformly dispersed in the plastic surgery filling composition prepared using the composite, and the biodegradable particles have a particle size that can effectively restore or replace human tissue, even if a thinner injection needle is used, only a small force needs to be applied to the syringe to successfully inject the plastic surgery filling composition.

[0042] <Formula 1>

[0043] PSD = (Dv(90) - Dv(10)) / Dv(50)

[0044] In the formula 1,

[0045] Dv(10) is the size of the biodegradable particles within 10% of the distribution (the size of the particles at the 10% position when the particle sizes are arranged from small to large based on the volume of the biodegradable particles distribution).

[0046] Dv(50) is the size of the biodegradable particles within 50% of the distribution (the particle size at the 50% position when the particle sizes are arranged from small to large based on the volume of the biodegradable particles).

[0047] Dv(90) is the size of the biodegradable particles within 90% of the distribution (the particle size at the 90% position when the particles are arranged from small to large based on the volume of the biodegradable particles).

[0048] Specifically, in Formula 1, Dv(10) may be 5 to 35 μm, 7 to 33 μm, 10 to 30 μm, 11 to 28 μm, 12 to 25 μm or 12 to 22 μm, Dv(50) may be 10 to 50 μm, 13 to 47 μm, 15 to 45 μm, 17 to 43 μm, 19 to 42 μm or 20 to 42 μm, and Dv(90) may be 20 to 90 μm, 25 to 85 μm, 27 to 82 μm, 29 to 80 μm, 30 to 78 μm or 32 to 75 μm, but are not limited thereto.

[0049] The biodegradable particles may be particles with a reticular structure inside. Specifically, the inside of the biodegradable particles may form a regular, irregular or combined three-dimensional network structure. Since the reticular structure exists inside the biodegradable particles, the biodegradable particles have high strength, thereby effectively repairing or replacing human tissue. In addition, since the biodegradable particles have high strength, the strength of the composite composed of the biodegradable particles will also increase, thereby improving the handling convenience of the composite.

[0050] The biodegradable particles may include common biodegradable polymers. Specifically, the biodegradable particles may include at least one selected from the group consisting of polylactic acid (PLA), polyglycolic acid (PGA), poly(D,L-lactic-co-glycolic acid) (PLGA), polycaprolactone (PCL), polyvalerolactone (PVL), polyhydroxybutyrate (PHB) and polyhydroxyvalerate (PBV), but are not limited thereto. Preferably, the biodegradable particles may be polylactic acid (PLA) particles.

[0051] The weight average molecular weight of the biodegradable particles may be 50,000 to 400,000 g / mol, but is not limited thereto. Specifically, the weight average molecular weight of the biodegradable particles may be 60,000 to 350,000 g / mol, 70,000 to 300,000 g / mol, 90,000 to 250,000 g / mol, 100,000 to 200,000 g / mol, 130,000 to 190,000 g / mol, or 150,000 to 180,000 g / mol. Since the weight average molecular weight of the biodegradable particles is within the above range, it is easy to process into a composite and the dispersibility of the composite can be improved.

[0052] The tap density of the biodegradable particles may be 0.1 to 0.25 g / ml, but is not limited thereto. Specifically, the tap density of the biodegradable particles may be 0.1 to 0.24 g / ml, 0.11 to 0.23 g / ml, 0.12 to 0.21 g / ml, 0.13 to 0.18 g / ml or 0.13 to 0.17 g / ml. Since the tap density of the biodegradable particles is within the above range, the biodegradable particles may be densely distributed in the composite, thereby increasing the strength of the composite and improving the dispersibility of the composite.

[0053] Water soluble polymer

[0054] According to the present invention, the water-soluble polymer contained in the composite has a carrier function for transporting the biodegradable particles, and a matrix function for dispersing and fixing the biodegradable particles.

[0055] The water-soluble polymer may include well-known polymers with water solubility. Specifically, the water-soluble polymer may include at least one selected from the group consisting of hyaluronic acid (HA), methylcellulose (MC), ethylcellulose (EC), carboxymethylcellulose (CMC), hydroxymethylcellulose (HMC), hydroxyethylcellulose (HEC), hydroxypropylcellulose (HPC), polyhydroxyethyl methacrylate (HEMA), polyvinyl alcohol (PVOH), polyvinyl pyrrolidone (PVP) and starch, but is not limited thereto. Preferably, the water-soluble polymer may be hyaluronic acid. Specifically, the water-soluble polymer may be non-cross-linked hyaluronic acid.

[0056] The hyaluronic acid can be a high molecular weight hyaluronic acid, such as sodium hyaluronate crosspolymer and sodium hyaluronate; a medium molecular weight hyaluronic acid, such as hydroxypropyltrimonium hyaluronate and sodium acetylated hyaluronate; a low molecular weight hyaluronic acid, such as potassium hyaluronate, hydrolyzed hyaluronic acid and hydrolyzed sodium hyaluronate; an ultra-low molecular weight hyaluronic acid, such as hyaluronic acid; or a combination thereof.

[0057] The weight average molecular weight of the water-soluble polymer may be 1,000,000 to 4,000,000 g / mol, but is not limited thereto. Specifically, the weight average molecular weight of the water-soluble polymer may be 1,200,000 to 4,000,000 g / mol, 1,300,000 to 4,000,000 g / mol, 1,500,000 to 4,000,000 g / mol, 1,800,000 to 4,000,000 g / mol, 2,000,000 to 4,000,000 g / mol, 2,100,000 to 3,800,000 g / mol or 2,200,000 to 3,600,000 g / mol. Since the weight average molecular weight of the water-soluble polymer is within the above range, it is easy to be processed into a composite and the dispersibility of the composite can be improved.

[0058] According to the present invention, the weight ratio of the biodegradable particles to the water-soluble polymer may be 40:60 to 95:5, but is not limited thereto. Specifically, the weight ratio of the biodegradable particles to the water-soluble polymer contained in the composite may be 45:55 to 95:5, 45:55 to 90:10, 50:50 to 90:10, 55:45 to 85:15, 60:40 to 85:15, 65:35 to 85:15, 70:30 to 85:15, 75:25 to 85:15, 80:20 to 85:15 or 70:30 to 80:20. Since the weight ratio is within the above range, the composite has good dispersibility and can be effectively used as a material for a plastic surgery filling composition.

[0059] Meanwhile, the composite according to the present invention may have a compressive strength of 0.02 to 1.5 MPa, but is not limited thereto. Specifically, the compressive strength of the composite according to the present invention may be 0.025 to 1.3 MPa, 0.03 to 1.2 MPa, 0.033 to 1.0 MPa, 0.035 to 1.0 MPa, 0.035 to 0.8 MPa, 0.035 to 0.6 MPa, 0.036 to 0.5 MPa, 0.036 to 0.45 MPa, 0.036 to 0.43 MPa, 0.037 to 0.4 MPa, 0.037 to 0.39 MPa, 0.037 to 0.38 MPa or 0.037 to 0.37 MPa.

[0060] In addition, the apparent volume of the composite according to the present invention can be 10 to 40 ml / g, but is not limited thereto. Specifically, the apparent volume of the composite according to the present invention can be 10 to 35 ml / g, 10 to 32 ml / g, 10 to 30 ml / g, 12 to 29 ml / g, 14 to 29 ml / g, 15 to 28 ml / g, 15.5 to 28 ml / g or 16 to 28 ml / g.

[0061] In addition, the porosity of the composite according to the present invention may be 90 to 97.5% by volume, but is not limited thereto. Specifically, the porosity of the composite according to the present invention may be 90 to 97% by volume, 90 to 96% by volume, or 90 to 95% by volume. The porosity may refer to the ratio of the pore volume present in the composite to the total volume of the composite.

[0062] Since the composite of the present invention has a compressive strength, an apparent density and a porosity within the above-mentioned specific ranges, it can have good long-term storage, handling convenience and dispersibility. In particular, since the composite according to the present invention contains the biodegradable particles with a controllable particle size distribution and the compressive strength is controlled within the above-mentioned specific range, when the composite is dispersed in a solvent for preparing a plastic surgery filling composition, it can be uniformly dispersed in a short time.

[0063] Specifically, the suspension time of the complex according to the present invention in an aqueous solvent can be 30 minutes or less, but is not limited thereto. Specifically, the suspension time of the complex according to the present invention in an aqueous solvent can be 1 to 30 minutes, 5 to 30 minutes, 10 to 30 minutes, 10 to 29 minutes, 10 to 25 minutes, 10 to 20 minutes or 12 to 19 minutes. At this time, the aqueous solvent can specifically be water, distilled water, deionized water, ultrapure water, etc., but is not limited thereto.

[0064] According to the present invention, the composite can have a cake formulation with a fluffy texture. Since the composite has a cake formulation, it can have good long-term storage properties and dispersibility in a solvent.

[0065] Specifically, the composite of the present invention may be cylindrical, but is not limited thereto. In addition, the average diameter of the composite may be 1 to 5 cm, 1 to 3 cm, 1 to 2.5 cm, 1.2 to 2.2 cm, or 1.5 to 2.0 cm, and the average height of the composite may be 0.2 to 5 cm, 0.3 to 3 cm, 0.5 to 3 cm, or 0.5 to 2.5 cm, but is not limited thereto.

[0066] Method for producing composite material

[0067] The present invention provides a method for manufacturing the composite. Specifically, the method for manufacturing the composite according to the present invention comprises the following steps: (1) dissolving a biodegradable raw material in a first solvent to prepare a biodegradable solution; (2) spraying the biodegradable solution into a second solvent having a freezing point lower than that of the first solvent to form biodegradable particles; (3) screening the biodegradable particles by size; (4) adding the biodegradable particles screened by size to a water-soluble polymer solution to prepare a mixed solution; (5) filling the mixed solution into a container; and (6) freeze-drying the mixed solution filled into the container to form a composite, for which reference is made to Figure 1 The following description is given.

[0068] The step (1) is a step of dissolving the biodegradable raw material in a first solvent to prepare a biodegradable solution. Specifically, the step (1) can be achieved by adding the biodegradable raw material to a first solvent mixed with two or more organic solvents and stirring.

[0069] Specifically, the biodegradable raw material may include at least one selected from the group consisting of polylactic acid (PLA), polyglycolic acid (PGA), poly(D,L-lactic-co-glycolic acid) (PLGA), polycaprolactone (PCL), polyvalerolactone (PVL), polyhydroxybutyrate (PHB) and polyhydroxyvalerate (PBV), but is not limited thereto.

[0070] The weight average molecular weight of the biodegradable raw material may be 50,000 to 400,000 g / mol, but is not limited thereto. Specifically, the weight average molecular weight of the biodegradable particles may be 60,000 to 350,000 g / mol, 70,000 to 300,000 g / mol, 90,000 to 250,000 g / mol, 100,000 to 200,000 g / mol, 130,000 to 190,000 g / mol, or 150,000 to 180,000 g / mol.

[0071] The first solvent can specifically be a combination of at least two substances selected from the following substances: dimethyl sulfoxide, diethyl sulfoxide, ethylene carbonate, propylene carbonate, dimethyl carbonate, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, N-hydroxyethyl-2-pyrrolidone, N-cyclohexyl-2-pyrrolidone, N-methylformamide, N,N-dimethylformamide, N-ethylformamide, N,N-ethylformamide, N-methylacetamide, N,N-dimethylacetamide, N,N-diethylacetamide, isopropyl acetate, ethyl acetate, methyl acetate, dimethyl ketone, diethyl ketone, methyl ethyl ketone, isopropyl ketone, methyl propyl ketone, methyl butyl ketone, methyl isobutyl ketone and tetrahydrofuran, but is not limited thereto.

[0072] Specifically, the first solvent may be a solvent in which the first organic solvent and the second organic solvent are mixed in a weight ratio of 70:30 to 98:2, 75:25 to 98:2, 80:20 to 95:5, 85:15 to 95:5, or 85:15 to 90:10. More specifically, the first solvent may be a mixed solvent of dimethyl sulfoxide and ethylene carbonate, but is not limited thereto.

[0073] The step (2) is a step of spraying the biodegradable solution into a second solvent having a lower freezing point than the first solvent to form biodegradable particles having a network structure inside. Specifically, the step (2) can be achieved by spraying the biodegradable solution into a second solvent, the second solvent is not mixed with the first solvent to achieve phase separation, and the freezing point of the second solvent is 5 to 150° C. (specifically, 90 to 120° C.) lower than the freezing point of the first solvent.

[0074] When spraying, the temperature of the second solvent may be specifically -45 to 0° C., -40 to -5° C., -35 to -10° C., or -30 to -10° C., but is not limited thereto. Since the temperature of the second solvent is within the above range, biodegradable particles having a desired particle size distribution and a network structure inside can be well formed.

[0075] The second solvent may be at least one selected from the group consisting of pentane, hexane, heptane, octane, nonane and decane, but is not limited thereto.

[0076] The spraying speed of the biodegradable solution into the second solvent may be 1 to 20 ml / min, 3 to 15 ml / min, or 5 to 10 ml / min, but is not limited thereto.

[0077] The step (3) is a step of screening the biodegradable particles according to size. Specifically, the step (3) can be achieved by feeding the biodegradable particles into a particle sorting machine to screen particles of a desired size.

[0078] Specifically, the particle size screening can be achieved by putting the biodegradable particles into a particle sorter using buoyancy. At this time, the particle size screening criteria are not particularly limited, and the particle size can be screened using Dv(50) (average particle size) of 10 to 60 μm (specifically 13 to 47 μm or 15 to 45 μm). Through this step, the particle size distribution of the biodegradable particles can be controlled within a specific range. When the biodegradable particles having a controllable particle size distribution are used to prepare a composite, a composite having good dispersibility in a solvent can be prepared.

[0079] The step (4) is a step of adding the biodegradable particles selected by size to a water-soluble polymer solution to prepare a mixed solution. Specifically, the step (4) can be achieved by adding the biodegradable particles selected by size to a water-soluble polymer solution with a controllable concentration and stirring.

[0080] The water-soluble polymer contained in the water-soluble polymer solution may specifically include at least one selected from the group consisting of hyaluronic acid (HA), methyl cellulose (MC), ethyl cellulose (EC), carboxymethyl cellulose (CMC), hydroxymethyl cellulose (HMC), hydroxyethyl cellulose (HEC), hydroxypropyl cellulose (HPC), polyhydroxyethyl methacrylate (HEMA), polyvinyl alcohol (PVOH), polyvinyl pyrrolidone (PVP) and starch, but is not limited thereto.

[0081] The weight average molecular weight of the water-soluble polymer may be 1,000,000 to 4,000,000 g / mol, but is not limited thereto. Specifically, the weight average molecular weight of the water-soluble polymer may be 1,200,000 to 4,000,000 g / mol, 1,300,000 to 4,000,000 g / mol, 1,500,000 to 4,000,000 g / mol, 1,800,000 to 4,000,000 g / mol, 2,000,000 to 4,000,000 g / mol, 2,100,000 to 3,800,000 g / mol, or 2,200,000 to 3,600,000 g / mol.

[0082] Based on the total weight of the water-soluble polymer solution, the content of the water-soluble polymer contained in the water-soluble polymer solution may be 0.2 to 2 wt%, 0.4 to 1.5 wt%, 0.5 to 1.3 wt%, 0.5 to less than 1 wt%, or 0.6 to 0.95 wt%, but is not limited thereto. Since the content of the water-soluble polymer is within the above range, the strength of the composite can be ensured while improving the dispersibility of the composite in the solvent.

[0083] The solvent contained in the water-soluble polymer solution may be a common aqueous solvent (such as water, distilled water, etc.), but is not limited thereto.

[0084] At the same time, the water-soluble polymer solution and the biodegradable particles may be mixed so that a weight ratio (a:b) of the water-soluble polymer (a) to the biodegradable particles (b) contained in the water-soluble polymer solution is 40:60 to 95:5, 45:55 to 95:5, 45:55 to 90:10, 50:50 to 90:10, 55:45 to 85:15, 60:40 to 85:15, 65:35 to 85:15, 70:30 to 85:15, 75:25 to 85:15, 80:20 to 85:15 or 70:30 to 80:20.

[0085] The step (5) is a step of filling the mixed solution into a container. Specifically, the step (5) can be achieved by filling the mixed solution into a specific container to form a composite having a cake-like dosage form.

[0086] The container may specifically be a sealable glass bottle (such as a vial), but is not limited thereto.

[0087] Based on the total volume of the container, the filling amount of the mixed solution in the container can be 10% to 80% by volume, 15% to 70% by volume, 15% to 65% by volume, 20% to 60% by volume, or 25% to 55% by volume, but is not limited thereto. Since the filling amount of the mixed solution is within the above range, a composite having a desired compressive strength can be formed in a cake-shaped dosage form.

[0088] The step (6) is a step of freezing the mixed solution filled in the container and then drying (evaporating) the solvent under vacuum to form a composite. Specifically, the step (6) may include the following steps: (6-1) freezing the mixed solution at -60 to -10°C to obtain a frozen product; (6-2) heating the frozen product to -5 to 5°C for a first time in a vacuum environment for 1 to 3 hours; (6-3) heating the frozen product heated for the first time to 20 to 25°C for a second time in a vacuum environment for 8 to 15 hours; and (6-4) drying the frozen product heated for the second time at 25°C or higher in a vacuum environment for 20 to 40 hours.

[0089] In the step (6-1), the temperature of freezing the mixed solution may be -60 to -10°C, -50 to -20°C or -40 to -30°C, but is not limited thereto. In addition, the time of freezing the mixed solution may be 60 to 240 minutes, 90 to 180 minutes or 120 to 150 minutes, but is not limited thereto.

[0090] The steps (6-2) to (6-4) are steps of drying (evaporating) the solvent present in the frozen product by gradually increasing the temperature of the frozen product. At this time, the final vacuum degree of each step can be 0.1 to 30 mtorr, 0.5 to 20 mtorr or 1 to 10 mtorr, but is not limited thereto.

[0091] Specifically, the step (6-2) can be achieved by a first heating process in a vacuum environment over 1 to 3 hours or 1.5 to 2.5 hours to raise the temperature of the frozen product from -60 to -10°C to -5 to 5°C, -3 to 3°C or -1 to 1°C.

[0092] The step (6-3) can be achieved by heating the frozen product after the first heating to 20 to 25°C, 22 to 25°C or 24 to 25°C for a second time in a vacuum environment for 8 to 15 hours or 9 to 11 hours.

[0093] The step (6-4) can be achieved by heating the frozen product after the second heating to 25°C or higher (specifically 25 to 30°C) in a vacuum environment for 20 to 40 hours or 22 to 30 hours, and finally drying it.

[0094] Since freeze-drying of the mixed solution is performed through the steps (6-1) to (6-4), a complex having a cake-like dosage form can be efficiently formed.

[0095] Meanwhile, the method for manufacturing the composite according to the present invention may further include a step of sterilizing the composite.

[0096] The sterilization may be achieved by gamma ray sterilization, electron beam (e-beam) sterilization, ethylene oxide sterilization, steam sterilization or high pressure steam sterilization, but is not limited thereto. Specifically, the sterilization may be achieved by using ethylene oxide at a temperature of 30 to 40° C. for 150 to 180 minutes. This process may further improve the long-term storage of the compound.

[0097] The size of the biodegradable particles contained in the composite prepared by the manufacturing method is not particularly limited, but the average particle size (Dv(50)) may be 15 to 60 μm. Specifically, the biodegradable particles may be first biodegradable particles whose Dv(50) particle size distribution is 15 to 30 μm, 17 to 29 μm, 18 to 28 μm, 19 to 27 μm, 20 to 25 μm or 21 to 23 μm; second biodegradable particles whose Dv(50) particle size distribution is greater than 30 to 60 μm, greater than 30 to 55 μm, 35 to 50 μm, 35 to 48 μm, 38 to 45 μm or 40 to 43 μm; or mixtures thereof, but are not limited thereto.

[0098] Specifically, according to the following Formula 1, the particle size distribution (PSD) of the biodegradable particles contained in the composite prepared by the manufacturing method can be 1.0 to 2.5, 1.0 to 2.3, 1.01 to 2.0, 1.02 to 1.9, 1.03 to 1.95, 1.04 to 1.9, 1.05 to 1.8, 1.05 to 1.6, 1.05 to 1.5, 1.08 to 1.4, 1.09 to 1.3 or 1.1 to 1.3, but is not limited thereto.

[0099] <Formula 1>

[0100] PSD = (Dv(90) - Dv(10)) / Dv(50)

[0101] In the formula 1,

[0102] Dv(10) is the size of the biodegradable particles within 10% of the distribution.

[0103] Dv(50) is the size within which 50% of the biodegradable particles are distributed.

[0104] Dv(90) is the size within which 90% of the biodegradable particles are distributed.

[0105] In the present invention, a composite is prepared by filling a mixed solution obtained by mixing biodegradable particles with a specific particle size distribution and a water-soluble polymer solution into a sealable container and freeze-drying the mixture, thereby obtaining a composite having a specific morphology of a cake-like dosage form and controllable compressive strength.

[0106] Since the composite of the present invention includes biodegradable particles with controllable particle size distribution and has a cake-like dosage form, it has good long-term storage and dispersibility, and can improve the convenience of handling by controlling the compressive strength. In addition, since the composite of the present invention includes biodegradable particles and a water-soluble polymer, it has cell compatibility and biodegradability.

[0107] Therefore, the composite according to the present invention can be well used as a material for restoring or replacing human tissue. In addition, the composite according to the present invention can also be used as a carrier of cells or drugs, a cell culture medium, etc.

[0108] Plastic surgery filling composition

[0109] The present invention provides a plastic surgery filling composition in which the composite is dispersed. Specifically, the plastic surgery filling composition according to the present invention may be a composition in which the composite having the same components and properties as above is dispersed in a solvent.

[0110] Due to the enhanced dispersibility of the composite, the plastic filling composition according to the present invention can be prepared in a short time (such as within 30 minutes). That is, due to the use of a sealed composite with a solid phase cake-like dosage form, the solubility and dispersibility are enhanced, and the plastic filling composition can be prepared in a short time. Therefore, the present invention is convenient for preparing the plastic filling composition immediately before the operation. In addition, since the composite contains biodegradable particles with a controllable particle size distribution, the plastic filling composition of the present invention obtained by dispersing it in a solvent can be easily completed by the operator with less force applied to the syringe even with a needle of a thinner diameter. Therefore, the plastic filling composition according to the present invention can reduce the discomfort and fatigue of the operator, while improving the operating environment.

[0111] For example, according to the plastic surgery filling composition of the present invention (for example, a composition in which a compound having an average particle size (Dv(50)) of 60 μm or less is dispersed), the injection force may be 2.0 N or less for an injection needle having a needle gauge (G) of 26, specifically, 0.3 to 1.5 N, 0.5 to 1.3 N, 0.7 to 1.25 N, or 0.9 to 1.20 N, but not limited thereto. In addition, according to the plastic surgery filling composition of the present invention (for example, a composition in which a compound having an average particle size (Dv(50)) of 33 μm or less is dispersed), for an injection needle having a needle gauge (G) of 30, the injection force may be 3.0 N or less, specifically, 1.6 to 2.6 N, 1.7 to 2.4 N, 1.8 to 2.2 N, or 1.9 to 2.0 N, but not limited thereto.

[0112] Mode for carrying out the invention

[0113] The present invention will be described in detail below by way of examples, but the scope of the present invention is not limited to these examples.

[0114] Example 1

[0115] 9 g of polylactic acid (PLA) with a weight average molecular weight of 170,000 g / mol was dissolved in 150 ml of a mixed solvent of dimethyl sulfoxide and ethylene carbonate in a weight ratio of 90:10 to prepare a polylactic acid solution.

[0116] Then, the prepared polylactic acid solution was sprayed into n-hexane cooled to -20°C or lower at a spraying amount of 4.5 ml / min and a spraying air amount of 6 L / min to form frozen polylactic acid particles in n-hexane. The formed frozen polylactic acid particles were added to water at 1 to 3°C and stirred to remove the mixed solvent (dimethyl sulfoxide + ethylene carbonate) contained in the frozen polylactic acid particles, thereby preparing polylactic acid particles (PLA particles).

[0117] Subsequently, the prepared polylactic acid particles were classified using a particle classifier to obtain polylactic acid particles having a particle size of 60 μm or less (Dv(50): 41.9 μm).

[0118] Then, polylactic acid particles having a particle size of 60 μm or less are added to a 0.6% sodium hyaluronate solution (HA solution = 99.4 wt % distilled water + 0.6 wt % sodium hyaluronate) so that the weight ratio of polylactic acid particles to sodium hyaluronate (HA) is 85:15, and then they are mixed to prepare a mixed solution.

[0119] Then, 5.20 g of the prepared mixed solution (170 mg PLA particles + 30 mg HA) was filled into a 10 ml vial.

[0120] Then, the mixed solution filled into the vial was frozen at a temperature of -40 to -30°C to obtain a frozen product. The obtained frozen product was first heated from -30°C to 0°C in a vacuum environment for 2 hours, then heated from 0°C to 25°C for 10 hours, and then dried at 25°C for 24 hours to form a complex in the vial.

[0121] Then, the vial containing the composite was sterilized using ethylene oxide (EO) gas, and residual moisture was removed by vacuum drying to prepare a composite having a diameter of 1.8 cm and a height of 2.2 cm.

[0122] Example 2 to Example 4

[0123] The composite was prepared by the same process as in Example 1, except that the concentration of sodium hyaluronate (HA) contained in the mixed solution filled in the vial, the filling amount of the mixed solution, and the diameter and height of the composite were adjusted as shown in Table 1 below.

[0124] [Table 1]

[0125]

[0126] Example 5

[0127] A composite having a diameter of 1.8 cm and a height of 0.55 cm was prepared by the same process as in Example 1, except that the polylactic acid particles were sorted using a particle sorter to obtain polylactic acid particles having a particle diameter of 33 μm or less (Dv(50): 21.1 μm), which were then added to a sodium hyaluronate solution.

[0128] Comparative Example 1

[0129] A composite with a diameter of 1.8 cm was prepared by the same process as in Example 1, except that the mixed solution (170 mg PLA particles and 30 mg HA) was filled into a vial and vacuum dried at 25° C. in a vacuum environment (5 mtorr) for 16 h (i.e., freeze drying and sterilization processes were not performed).

[0130] Comparative Example 2

[0131] A composite having a diameter of 1.8 cm and a height of 2.2 cm was prepared by the same process as in Example 1, except that the polylactic acid particles were sorted using a particle sorter to obtain polylactic acid particles having a particle diameter of 300 μm or less (Dv(50): 41.7 μm), which were then added to a sodium hyaluronate solution.

[0132] Experimental Example 1. Particle size distribution measurement

[0133] The particle size distribution of the polylactic acid particles prepared in Example 1, Example 5 and Comparative Example 2 was measured according to the following measurement method. The results are shown in Table 2 below.

[0134] * Particle size distribution determination method

[0135] 1) Add the complex into water and stir for 30 minutes to prepare a suspension.

[0136] 2) The prepared suspension was analyzed using a particle size distribution analyzer (manufacturer: Malvern Instrument, model: Mastersizer 3000-Maz 6140) to determine the particle size distribution of the polylactic acid particles.

[0137] 3) According to the values ​​measured in step 2), the particle size distribution (PSD) is calculated using the following formula 1.

[0138] <Formula 1>

[0139] PSD = (Dv(90) - Dv(10)) / Dv(50)

[0140] In the formula 1,

[0141] Dv(10) is the size of the biodegradable particles within 10% of the distribution.

[0142] Dv(50) is the size within which 50% of the biodegradable particles are distributed.

[0143] Dv(90) is the size within which 90% of the biodegradable particles are distributed.

[0144] [Table 2]

[0145] distinguish Dv(10) Dv(50) Dv(90) Particle size distribution Example 1 20.9μm 41.9μm 73.9μm 1.265 Example 5 11.6μm 21.1μm 34.4μm 1.081 Comparative Example 2 13.1μm 41.7μm 140μm 3.043

[0146] Referring to Table 2 above, it can be confirmed that the particle size distribution range of the polylactic acid particles prepared in Example 1 and Example 5 is 1.0 to 2.5. Among them, since the particle size distribution of the polylactic acid particles is within the above range, the present invention can improve the convenience of use (practicality) of the composite. That is, when the particle size distribution is within the above range, the dispersibility of the composite is good, and even if a small force (injection force) is applied to the syringe containing the suspension dispersed with the composite, the suspension can be discharged smoothly, which can be confirmed in the following Experimental Examples 7 and 8.

[0147] Meanwhile, it can be confirmed that the particle size distribution range of the polylactic acid particles prepared in Comparative Example 2 is 1.0 to 2.5.

[0148] Experimental Example 2. Determination of tap density

[0149] In Example 1 and Example 5, respectively, the tap density of the polylactic acid (PLA) particles obtained by sorting with a particle sorter was measured according to the following measurement method. The results are shown in Table 3 below.

[0150] *Tap density determination method

[0151] 1) Measure the weight of a measuring cylinder and add 20 to 25 ml of polylactic acid particles into the measuring cylinder.

[0152] 2) Determine the weight of the measuring cylinder containing the polylactic acid particles and calculate the weight of the pure polylactic acid particles.

[0153] 3) The measuring cylinder containing the polylactic acid particles was mounted on a tap density tester (manufacturer: Bettersize, model: BeDensi T1 Pro).

[0154] 4) The tap density tester was operated at a tapping speed of 250 times / min and a tapping frequency of 1,250 times.

[0155] 5) After compaction, take out the measuring cylinder and measure the volume of the polylactic acid particles.

[0156] 6) Divide the weight of the polylactic acid particles measured in step 2) by the volume of the polylactic acid particles measured in step 5) to calculate the tap density (measure the tap density of 5 samples separately and take the average value).

[0157] [Table 3]

[0158]

[0159] Referring to Table 3 above, it can be confirmed that the tap density of the polylactic acid particles prepared in Example 1 and Example 5 is between 0.1 and 0.2 g / ml. Among them, in Example 5 where the particle size of the polylactic acid particles is smaller than that of Example 1, the tap density of the polylactic acid particles is larger, and high-density bonding is expected to be achieved inside the composite.

[0160] Experimental Example 3. Compressive Strength Determination

[0161] The compressive strength of the composites prepared in Examples 1 to 4 and Comparative Examples 1 and 2 was measured using an Instron 5848 (model name) instrument (measurement conditions - compression speed: 10 mm / min, maximum compression rate: 75%). The results are shown in Table 4 below.

[0162] [Table 4]

[0163] distinguish HA concentration (%) Compressive strength(MPa) Example 1 0.6 0.03750 Example 2 0.8 0.36316 Example 3 1.0 0.50605 Example 4 1.2 0.94671 Comparative Example 1 0.6 Unable to measure (irregular shape) Comparative Example 2 0.6 0.01998

[0164] Referring to Table 4 above, it can be confirmed that the compressive strength of the composites in Examples 1 to 4 is between 0.03 and 1 MPa. In addition, it can be seen that the concentration of sodium hyaluronate (HA) has an effect on the compressive strength of the composite.

[0165] Meanwhile, it can be confirmed that the compressive strength of the composite of Comparative Example 2 is lower than that of the composites of Examples 1 to 4. In addition, since the composite of Comparative Example 1 has an irregular shape, the compressive strength cannot be measured.

[0166] Experimental Example 4. Apparent volume measurement

[0167] The apparent volumes of the composites prepared in Examples 1 to 4 and Comparative Example 1 were measured using the diameter and height of the composites. The results are shown in Table 5 below.

[0168] [Table 5]

[0169]

[0170]

[0171] Referring to Table 5 above, it can be confirmed that the apparent volume of the composites in Examples 1 to 4 ranges from 10 to 40 ml / g. In addition, it can be predicted that in order to improve the porosity of the composite, it is best to reduce the concentration of sodium hyaluronate (HA). Among them, if the composite has a higher porosity, it can be quickly suspended in an aqueous solvent for use, thereby improving the convenience of use of the composite, which can be confirmed in the following Experimental Examples 7 and 8.

[0172] Meanwhile, since the composite of Comparative Example 1 has an irregular shape, the apparent volume cannot be determined.

[0173] Experimental Example 5. Dosage Form Confirmation

[0174] The dosage forms of the composites prepared in Examples 1, 5 and Comparative Example 1 were visually confirmed. Figure 2 shown.

[0175] Reference Figure 2 , it can be confirmed that the composites of Example 1 and Example 5 are in a cake-like dosage form (cylindrical). In contrast, it can be confirmed that the composite of Comparative Example 1 does not have a regular shape because the mixed solution expands during the vacuum drying process.

[0176] Among them, since the complexes in Example 1 and Example 5 have a cake-like dosage form, the present invention can improve the dispersibility and ease of use of the complexes. This can be confirmed in the following Experimental Examples 7 and 8.

[0177] Experimental Example 6. Confirmation of the internal structure of polylactic acid particles and the structure of the composite

[0178] The composites prepared in Example 1 and Example 5 were cut vertically, and the cross-sections were observed using a scanning electron microscope (manufacturer: Hitachi High Technologies, model: Hitachi su5000). Figure 3 and Figure 4 shown.

[0179] Refer to Figure 3 and Figure 4 a), it can be confirmed that in the composites of Example 1 and Example 5, the polylactic acid particles each maintain their shape and are uniformly present inside the composite. Figure 3 and Figure 4 From b), it can be confirmed that the polylactic acid particles present in the composites of Examples 1 and 5 have a network structure inside.

[0180] Experimental Example 7. Suspension time measurement

[0181] The suspension time of the complexes prepared in Examples 1 to 4 was measured respectively according to the following measurement method. The results are shown in Table 6 below.

[0182] * Suspension time determination method

[0183] 1) Add 8 ml of distilled water to the vial containing the complex and let it stand for about 5 minutes.

[0184] 2) After setting the rotation speed (rpm) of the vortex stirrer to 3,000, stir the vial for 5 minutes.

[0185] 3) Visually confirm whether the complex in the vial is completely dissolved and granulated.

[0186] 4) Repeat the process of step 2) until the complex is completely dissolved, and measure the time required for its granulation.

[0187] [Table 6]

[0188]

[0189] Referring to Table 6 above, it can be confirmed that the complexes in Examples 1 to 4 are rapidly suspended (dispersed) within a suspension time of 30 minutes or less. Since the suspension is completed in a short time, the complex of the present invention has excellent convenience in use. For example, when the complex is suspended in an aqueous solvent at the operation site for skin surgery, it can be suspended in a short time, thereby improving the efficiency of the operation.

[0190] Among them, since the composite of the present invention has a cake-like dosage form, and the particle size distribution, compressive strength and apparent volume are within a specific range, it can be suspended in a short time, which proves the importance of controlling the shape, compressive strength, apparent volume and particle size distribution of the composite.

[0191] Furthermore, it was confirmed that the lower the concentration of sodium hyaluronate (HA), the shorter the suspension time. Therefore, in order to improve the ease of use of the composite, it is best to control the concentration of hyaluronic acid that forms the composite support structure (framework).

[0192] Experimental Example 8. Injection force measurement

[0193] The injection force of the composites prepared in Example 1, Example 5 and Comparative Example 2 was measured according to the following measurement method. The results are shown in Table 7 below.

[0194] *Injection force measurement method

[0195] 1) Add 5 ml of distilled water to the vial containing the complex and stir with a vortex mixer until the complex is completely dissolved and granulated (suspension preparation).

[0196] 2) Inject 0.5 to 0.6 ml of the suspension in the vial into a 1 ml disposable syringe.

[0197] 3) Install a 26G or 30G injection needle on the syringe, and fix the syringe on the bracket of the universal material testing machine (manufacturer: TestOne, model: TO-102) with the needle facing downward.

[0198] 4) Operate the universal material testing machine, press the push rod on the syringe at a speed of 1 mm / s until the syringe is completely empty, and record the measured force.

[0199] 5) In the graph recording the measured forces, calculate the average value (injection force) of the forces measured at 5 mm to the right of the starting point, 5 mm to the left of the end point, and the midpoint between the two points.

[0200] [Table 7]

[0201]

[0202] Referring to Table 7 above, it can be confirmed that the injection force of the complexes of Example 1 and Example 5 is small, and therefore, even if a small injection force is applied, the suspension in which the complex is dispersed can be smoothly discharged from the syringe. It can be seen from this that due to the small injection force, the complex of the present invention has excellent convenience in use. For example, when the suspension in which the complex is dispersed is used at the operation site, even if a small force is applied to the syringe, the suspension can be smoothly discharged from the syringe and injected into the skin, and thus, the convenience of operation can be improved.

[0203] Meanwhile, the composite of Comparative Example 2 has a large particle size when dispersed, so the suspension dispersed with the composite of Comparative Example 2 cannot pass through the injection needle, resulting in blockage, and thus the injection force cannot be measured. It can be seen from this that the suspension dispersed with the composite of Comparative Example 2 is difficult to use at the operation site.

[0204] The above results demonstrate the importance of controlling the shape, compressive strength, apparent volume and particle size distribution of PLA particles in the composites.

Claims

1. A composite comprising: Biodegradable particles; as well as Water-soluble polymers, The particle size distribution (PSD) of the biodegradable particles according to the following formula 1 is 1.0 to 2.5, <Formula 1> PSD = (Dv(90) - Dv(10)) / Dv(50) In the formula 1, Dv(10) is the size of the biodegradable particles within 10% of the distribution. Dv(50) is the size within which 50% of the biodegradable particles are distributed. Dv(90) is the size within which 90% of the biodegradable particles are distributed.

2. The composite according to claim 1, wherein The compressive strength of the composite is 0.02 to 1.5 MPa.

3. The composite according to claim 1, wherein In Formula 1, Dv(10) is 5 to 35 μm, and Dv(90) is 20 to 90 μm.

4. The composite according to claim 1, wherein The apparent volume of the complex is 10 to 40 ml / g.

5. The composite according to claim 1, wherein The biodegradable particles have a mesh structure inside.

6. The composite according to claim 1, wherein The biodegradable particles are at least one selected from the group consisting of polylactic acid, polyglycolic acid, poly(D,L-lactic-co-glycolic acid), polycaprolactone, polyvalerolactone, polyhydroxybutyrate and polyhydroxyvalerate.

7. The composite according to claim 1, wherein The water-soluble polymer is at least one selected from the group consisting of hyaluronic acid, methyl cellulose, ethyl cellulose, carboxymethyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, polyhydroxyethyl methacrylate, polyvinyl alcohol, polyvinyl pyrrolidone and starch.

8. The composite according to claim 1, wherein The suspension time of the complex in the aqueous solvent is 30 minutes or less.

9. A method for producing a composite, comprising the following steps: (1) dissolving a biodegradable raw material in a first solvent to prepare a biodegradable solution; (2) spraying the biodegradable solution into a second solvent having a freezing point lower than that of the first solvent to form biodegradable particles; (3) screening the biodegradable particles by size; (4) adding the biodegradable particles screened by size to a water-soluble polymer solution to prepare a mixed solution; (5) filling the mixed solution into a container; as well as (6) freeze-drying the mixed solution filled in the container to form a complex, The particle size distribution of the biodegradable particles contained in the composite is 1.0 to 2.5 according to the following formula 1, <Formula 1> PSD = (Dv(90) - Dv(10)) / Dv(50) In the formula 1, Dv(10) is the size of the biodegradable particles within 10% of the distribution. Dv(50) is the size within which 50% of the biodegradable particles are distributed. Dv(90) is the size within which 90% of the biodegradable particles are distributed.

10. The method for producing a composite according to claim 9, wherein: The freeze-drying of the mixed solution in step (6) comprises the following steps: (6-1) freezing the mixed solution at -60 to -10°C to obtain a frozen product; (6-2) in a vacuum environment, heating the frozen product to -5 to 5° C. for a first time for 1 to 3 hours; (6-3) heating the frozen product heated for the first time to 20 to 25° C. for a second time in a vacuum environment for 8 to 15 hours; and (6-4) The second heated frozen product is dried at 25° C. or higher for 20 to 40 hours in a vacuum environment.

11. The method for producing a composite according to claim 9, wherein: In the step (4), the content of the water-soluble polymer in the water-soluble polymer solution is 0.2 to 2 weight % of the total weight of the water-soluble polymer solution.

12. A plastic surgery filling composition, wherein: The composite according to any one of claims 1 to 8 is dispersed.

13. The plastic surgery filling composition according to claim 12, wherein The injection force of the plastic surgery filling composition is 2.0 N or less for an injection needle having a needle gauge of 26.